ChemInform Abstract: Synthesis of 6‐s‐Cis and 6‐s‐Trans A‐Ring Modified Vitamin D Analogues. Issue 45 (November 2015) - Fernandez, Susana; Hernandez‐Martin, Alba; Gonzalez‐Garcia, Tania; Ferrero, Miguel
Abstract Review: 143 refs.